2011
DOI: 10.1007/s00296-011-1810-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased myeloperoxidase plasma levels in rheumatoid arthritis

Abstract: High myeloperoxidase (MPO) serum levels have been shown in several inflammatory diseases, including rheumatoid arthritis (RA). However, the correlation between MPO levels and disease activity in RA patients is still controversial. The aim of the study was to determine MPO plasma levels in RA patients and to investigate potential correlations between MPO levels and disease activity and treatment. MPO plasma levels were measured by ELISA according the manufacturer's instructions. Disease activity was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 18 publications
3
28
2
Order By: Relevance
“…The significance of serum MPO in RA has been reported in a few recently published studies, and the associations between serum MPO levels and disease variables are still controversial (Stamp et al, 2012;Fernandes et al, 2012). In the present study, we observed that serum MPO levels were associated with disease activity indicators in RA patients, and that increased MPO concentrations were more likely to occur in patients with higher DAS28, and those with elevated inflammatory indicators (CRP, and the neutrophil percentage).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The significance of serum MPO in RA has been reported in a few recently published studies, and the associations between serum MPO levels and disease variables are still controversial (Stamp et al, 2012;Fernandes et al, 2012). In the present study, we observed that serum MPO levels were associated with disease activity indicators in RA patients, and that increased MPO concentrations were more likely to occur in patients with higher DAS28, and those with elevated inflammatory indicators (CRP, and the neutrophil percentage).…”
Section: Discussionmentioning
confidence: 60%
“…In addition, both plasma MPO and MPO in synovial fluid were proved to be active in their study. By contrast, another previous study found no significant association between serum MPO and DAS28, although they observed increased MPO plasma levels in RA patients (Fernandes et al, 2012). The patient cohort analyzed by Fernandes et al included only 57 female patients with RA from Latin America, thus their study might have lacked statistical power on account of the relatively small study population.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This concept is supported by the finding that both intracellular and extracellular MPO was shown to be present in the synovium of RA patients [82]. In addition, RA patients were shown to have increased plasma levels of MPO compared to healthy controls [83,84]. However, there was inconsistency as to the correlation between MPO levels in the plasma and disease activity score, as one study showed correlation, while another did not [83,84].…”
Section: Mpo and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…RA is associated with altered pro-inflammatory HDL22 23 and increased MPO level and activity 24 25. Impaired RCT has been reported in RA patients with high disease activity and levels of plasma MPO correlated with this impairment 26.…”
Section: Introductionmentioning
confidence: 99%